2018
DOI: 10.1080/09273948.2018.1484492
|View full text |Cite
|
Sign up to set email alerts
|

Change in Nationwide Incidence of Post-Cataract Surgery Endophthalmitis: Korean Cohort Study from 2002 to 2013

Abstract: This study revealed the incidence of endophthalmitis decreased during a 12-year period, but remained constant in diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
3
4
0
Order By: Relevance
“…Our findings are in agreement with the results of recent studies from other countries, which showed a significant decrease in the incidence of POE after cataract surgery over time [6,7,13,14,15]. The results of the recent studies of POE which comprised over 100,000 participants are presented in Table 6.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are in agreement with the results of recent studies from other countries, which showed a significant decrease in the incidence of POE after cataract surgery over time [6,7,13,14,15]. The results of the recent studies of POE which comprised over 100,000 participants are presented in Table 6.…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of endophthalmitis decreased significantly in the three periods of the 12 years, and it was significantly lower than 0.033% reported by large ophthalmology institutions in China in the past 3 years. It was similar to the results of Oh et.al 7 about big data of cataract surgery in South Korea from 2002 to 2013.…”
Section: Discussionsupporting
confidence: 90%
“…As a consequence, there was no correlation analysis in this study. In this study, univariate analysis showed that behindthe-lens washout during cataract surgery had a significant effect on inhibiting the incidence of postoperative preventing endophthalmitis, which was consistent with the view of Oshika et al 30 In cataract extraction, it is necessary to remove the ophthalmic viscoelastic agent to prevent high intraocular pressure, but behind-the-lens washout can more sufficient to clean the surface of IOL, because studies 7,9,[31][32][33] showed bacteria could adhere to the surface of ophthalmic instruments and IOL, increasing the risk of endophthalmitis, especially hydrophobic IOL.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings are in agreement with the results of the recent studies from other countries, which showed a significant decrease in the incidence of POE after cataract surgery over time. [6,7,13,14,15] The results of the recent studies of POE which comprised over 100 000 participants are presented in Table 6. Our total incidence rate of POE (0.109%) was similar to the rate found in a nationwide study in France.…”
Section: Discussionmentioning
confidence: 99%